Kajian Biaya Perawatan Jalan Perkebunan Kelapa Sawit (Elaeis Guineensis Jacq) Di Divisi 1 Kebun Bah Bulian PT.PP.London Sumatra Indonesia, TBK - Roosmawati, Febriana (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
Oil palm is a plantation commodity that has the potential to fill the market opportunities both domestically and internationally. This prospect encourages Bah Bulian Plantation to undertake road maintenance. The Bah Bulian plantation is engaged in the oil palm commodity. This study aims to determine the cost of manual and mechanical road maintenance which implemented at Bah Bulian Plantation, PT.PP. London Sumatra Indonesia Tbk. Raya Kahean, Simalungun Regency, North Sumatra Province. The research was conducted from June to August, 2020. This research is used descriptive analysis method which outlines the cost of road maintenance in Division 1 Bah Bulian Plantation PT.PP. London Sumatra Indonesia Tbk. The area of Division 1 Bah Bulian Plantation is 526.52 Ha. The type of road in Division 1 is a 36,919 meter long transport road or an average length of 45.7 meters. Mechanical and manual road maintenance costs which conducted in Division 1 Bah Bulian Plantation in 2017 at a cost of Rp. 76,662,936 for a cost of Rp. 145,470 / Ha, and in 2018 at a cost of Rp. 90,996,408 for a cost of Rp. 172,668 / Ha, and in 2019 requires a fee of Rp. 80,550,936 for a cost of Rp. 152,848 / Ha